2018
DOI: 10.1519/jsc.0000000000001799
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Among Repeated Sprint Ability, Chronological Age, and Puberty in Young Soccer Players

Abstract: Perroni, F, Pintus, A, Frandino, M, Guidetti, L, and Baldari, C. Relationship among repeated sprint ability, chronological age, and puberty in young soccer players. J Strength Cond Res 32(2): 364-371, 2018-The aim of this study was to analyzed the relationship of repeated sprint ability (RSA) with chronological age and puberty in 100 young soccer players (age: 13 ± 3 years-160 ± 33 months-; height: 159 ± 16 cm, mass: 49.7 ± 14.1 kg; body mass index [BMI] 19.2 ± 2.5 kg/m) grouped on "Pulcini" (9-10 years), "Eso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…Therefore, these outcomes suggest that the speed training should be more specific from the U16 age category onwards. Whereas, the use of RSA protocols for talent identification should be applied once players surpass the peak height velocity period (Perroni et al, 2018b; Selmi et al, 2018). It is important to consider that the characteristics of each repeated-sprint ability test (recovery duration, number of sprints, distance, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, these outcomes suggest that the speed training should be more specific from the U16 age category onwards. Whereas, the use of RSA protocols for talent identification should be applied once players surpass the peak height velocity period (Perroni et al, 2018b; Selmi et al, 2018). It is important to consider that the characteristics of each repeated-sprint ability test (recovery duration, number of sprints, distance, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that our findings were affected by the lower repeated-sprint ability of the U14 and U18 groups included in our study. Perroni et al (2018b) found a great variability in physical parameters like speed time even in young soccer players from the same category. Therefore, training loads should be in line with the individual maturity status of these players.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, nutrition depends on the relationship between energy production and its consumption in the human body [19]. Puberty is a succession of anatomical and physiological changes in early adolescence that mark the transition period from sexually immature to fully mature and is characterized by the development of reproductive functions, changes in body size, composition and function in response to sex hormones [20]. If in this period intensive growth…”
Section: Discussionmentioning
confidence: 99%
“…In the sports context, the players are grouped into categories by chronological age with two years in each group. 14 Considering that the age of the individual does not necessarily correspond with the pubertal stage, this suggests that individuals in different pubertal stages within a category may present different performances in the specific motor movements of the modality, and that prepubertal individuals do not necessarily present a lack of ability in the sport. 8,20 Jump performance in the sports context, vertical jumping tests are widely used for training 21,22 and evaluation of muscle strength and lower limb power through the jumping height reached, the squat jump (SJ) and counter-movement jump (CMJ) being the main vertical tests used in the literature.…”
Section: Introductionmentioning
confidence: 99%